Sustainable energy recovery from thermal processes: a review - Weidong Chen; Zhifeng Huang; Kian Jon Chua (Energy, Sustainability and Society, 2022)
Highlights 1. Industrial waste heat supply technologies and their exhaust features are reviewed. 2. Waste thermal heat recovery technologies are summarized and reviewed. 3. Thermal cold energy recovery technologies are summarized and reviewed. 4. Challenges and prospects of sustainable energy recovery are analyzed.